Eruptive Syringoma: Two Cases with Dermoscopic Features - Botsali, Aysenur (Skin Appendage Disord, 2020)
Syringoma is an adnexal tumor typically observed on the periorbital region and readily diagnosed by clinical examination. Eruptive syringoma is a rare variant that is commonly confused with mastocytosis and lichen planus clinically. The diagnosis is generally confirmed by typical histopathological features. Herein, we report two eruptive syringoma cases along with the dermoscopic features. Through our dermoscopic evaluation before skin biopsy, we detected features also reminding that of maculopapular mastocytosis as reticular light brown lines, structureless light-brown areas, and reticular vessels. Additionally, as an additional pattern, shiny white dots were observed in the vulvar variant.